(untitled) (Sebha University Conference Proceedings, 2022)
Corruption The twenty–first century is the area of the explosion of the information revolution. The world has changed into an electronics village, lies on the electronic nature of the emergence of technology. Society has exchanged opinions and ideas across cross-border temporal and spatial. Many spread modern technologies such as computers, the internet and mobile phones started to be used, despite the many public life and education in particular. However, it has many negative effects on human life and natural phenomena (land-water and air). Excessive use of modern technical devices and attachment to them to the point of electronic addiction corrupts society. This deadly hidden weapon corrupted people and worked to distort the Islamic religion. The study aimed at the philosophy of educational technology and its negative effects on the knowledge-building of society and that the issue of accepting or rejecting technology is no longer optional but rather a matter of awareness of the importance of information technology which turned the scales from positive effects to negative effects corrupting society. Here lies the question, how to confront the challenge and address the negative effects resulting from the misuse of technology? In this research, we explained the extent of society’s contribution to spreading technological awareness. We develop solutions to reduce technology risks and knowing the most important problems that obstruct the benefit from the assistances of technology. This done is order to achieve the benefits of the descriptive analytical approach to suit the nature of the research through which the information was analysed to reach desired results and some recommendations.